2003
DOI: 10.1159/000069841
|View full text |Cite
|
Sign up to set email alerts
|

Preventive (Evidence-Based) Approach to Quality General Dental Care

Abstract: Restorative and scaling treatments have not generally provided an effective method for managing dental caries and periodontal diseases. Rather, restorative treatment has often covered up the disease processes in the short term and created a new problem: that of maintenance and re-restoration of restored teeth. Thus, standard invasive dental treatments that are commonly provided fail to address the fundamental bacterial nature of the diseases. Indeed, these treatments rather readily generate and perpetuate a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 24 publications
0
56
0
5
Order By: Relevance
“…This is because tooth losses have a cohort effect, since they accumulate over the lifetime of individuals, without any natural association with aging, but due to the aggravation of oral diseases 5 . Not associating the access The fact of access to public or private dental services not being associated with tooth loss could be explained by both the easy access to the services, and by individuals' exclusion from them: because this could culminate in overtreatment and repetitive restorative cycles 23 , or delayed request for and access to dental care, with progression of the disease, respectively, resulting in tooth extraction as the only treatment option 24 .…”
Section: Discussionmentioning
confidence: 99%
“…This is because tooth losses have a cohort effect, since they accumulate over the lifetime of individuals, without any natural association with aging, but due to the aggravation of oral diseases 5 . Not associating the access The fact of access to public or private dental services not being associated with tooth loss could be explained by both the easy access to the services, and by individuals' exclusion from them: because this could culminate in overtreatment and repetitive restorative cycles 23 , or delayed request for and access to dental care, with progression of the disease, respectively, resulting in tooth extraction as the only treatment option 24 .…”
Section: Discussionmentioning
confidence: 99%
“…This 'rational' model of care is known as minimal intervention dentistry and is applicable not only to cariology but to periodontology and all other areas of dentistry. [1][2][3] Studies conducted in France in the early 2000s indicated that dental practitioners had not yet integrated this concept of cariology into practise [4][5][6][7] even though, since the 1990s, Elderton had already denounced traditional approaches to conservative dentistry when considered in isolation. [8][9][10] Indeed, traditional oral care, which comprises largely conservative/ operative dentistry, including scaling and polishing, has very little impact on the oral health of patients both in children and adults because the patient finds himself/ herself caught in a repeat restoration spiral of care, where successive replacement…”
Section: Verifiable Cpd Papermentioning
confidence: 99%
“…2,8,11,12 Figure 1 illustrates a patient, aged 33 at the time of the photograph, who has, judging by the number of endodontic treatments present, been obliged to visit the dentist on numerous occasions in the past. The problem of oral hygiene has not been resolved and, the caries process, which is very aggressive, has not been halted.…”
Section: Introductionmentioning
confidence: 99%
“…Technology without purpose does not improve human health and well-being. As researchers, academicians, and clinicians, we need to continue to change the way in which dentistry is delivered, with more emphasis on prevention and intervention as the forerunner to necessary restorative work (Featherstone, 1999;Elderton, 2003;Fontana and Wolff, 2011). We need to target improved remineralization technology and anticaries agents to those who most need it.…”
Section: Rationale Behind the Icnara Meetingsmentioning
confidence: 99%